Identification of potential indoor air pollutants in schools. (1st January 2020) - Becerra, Jose A.; Lizana, Jesus; Gil, Maite; Barrios-Padura, Angela; Blondeau, Patrice; Chacartegui, Ricardo
Abstract: Indoor air quality in school buildings plays an important role in students' wellbeing and performance. The presence and evolution of different compounds are directly affected by indoor activities, classroom materials and equipment, along with outside conditions derived from location and surrounding activities. Despite high CO2 concentration levels in classrooms being regulated in some regions, there is a wide range of pollutant substances that should be considered. This paper analyses a wide spectrum of air pollutants in school buildings to identify their relative impact and relevance. Measured values are compared to the recommended indoor air guideline values (IAGVs) reported in different national regulations and health organisations. This characterisation helps to evaluate the impact of potential indoor and outdoor air pollutant sources in schools; to define appropriate criteria to analyse the exposure to a wide range of air pollutants; and to develop appropriate strategies in order to reduce the exposure to air pollutants and minimise adverse health effects. A set of high priority pollutants, such as CO2, PM2.5, PM10, TVOC and a set of specific aldehydes and volatile organic compounds, were monitored through active and passive measurement in 18 classrooms of 9 Mediterranean schools. These schools were selected according to their construction period, design typology, and students' ages. The measurements taken during teaching hours show mean CO2 concentration values of 1530 ppm, oscillating in a range from −24% to +31%. The analysis highlights that along with occupancy, the main indoor air pollutant sources in schools are related to settled dust that produces suspension particles during classroom activity, affecting the relative differences in the mean PM concentration value from +36% to +193%. Moreover, aldehydes show high concentration values in infant classrooms, showing relative differences in the mean value from +163% to +313%. Additionally, the study demonstrates that outdoor air pollutant sources in school surroundings, such as high-density traffic areas or industrial activities, play an important role in final indoor air quality performance, affecting PM10, PM2.5, TVOC, benzene and toluene levels. The measurements show good indoor air quality values, below the recommended indoor air quality guidelines, but they also highlight the monitoring interest of some specific compounds for future regulations, such as PM2.5, PM10, TVOC, benzene, toluene or formaldehyde. Highlights: Identification of main indoor air pollutants in school environments. Indoor air pollutants are measured and analysed in 18 classrooms. They were monitored through active and passive measurement techniques. Exceedances over the mean and recommended values are highlighted. Design criteria and strategies are identified to ensure an adequate air quality.